2014
DOI: 10.1186/s12989-014-0038-4
|View full text |Cite
|
Sign up to set email alerts
|

Topically applied ZnO nanoparticles suppress allergen induced skin inflammation but induce vigorous IgE production in the atopic dermatitis mouse model

Abstract: BackgroundMetal oxide nanoparticles such as ZnO are used in sunscreens as they improve their optical properties against the UV-light that causes dermal damage and skin cancer. However, the hazardous properties of the particles used as UV-filters in the sunscreens and applied to the skin have remained uncharacterized.MethodsHere we investigated whether different sized ZnO particles would be able to penetrate injured skin and injured allergic skin in the mouse atopic dermatitis model after repeated topical appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(75 citation statements)
references
References 36 publications
1
74
0
Order By: Relevance
“…This is particularly true for TiO 2 , CeO 2 and ZnO NPs that were found to induce inflammation in some studies [37][38][39][40], whereas they were found to possess anti-inflammatory properties in others [41][42][43]. This illustrates how complex is the study of NPs in in vivo biological systems.…”
Section: Discussionmentioning
confidence: 86%
“…This is particularly true for TiO 2 , CeO 2 and ZnO NPs that were found to induce inflammation in some studies [37][38][39][40], whereas they were found to possess anti-inflammatory properties in others [41][42][43]. This illustrates how complex is the study of NPs in in vivo biological systems.…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, although it is still under debate, the effects of ZnO NPs on the immune system have been raised in some studies (Kim et al, ; Roy et al, ). For example, topical application of ZnO NPs reduced local skin inflammation but induced systemic production of IgE antibodies in the atopic dermatitis model (Ilves et al, ). Additionally, ZnO NPs (750 mg/kg/day) administered orally for 14 days suppressed innate immunity without an effect on the T cell‐mediated immune response, the ratio of CD4+/CD8+, subtypes of T cells, was slightly reduced, and serum levels of pro‐, anti‐, and Th1 type‐inflammatory cytokines were significantly inhibited in mice exposed to ZnO NPs compared to the control (Kim et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Total and timothy‐specific antibodies were measured by the ELISA method as previously described . The standard BD Pharmingen sandwich protocol was used to quantify the total amounts of IgE, IgG1 and IgG2a in mice sera.…”
Section: Methodsmentioning
confidence: 99%